Poly(styrene-co-butadiene) random copolymer thin films and nanostructures on a mica surface: morphology and contact angles of nanodroplets. Issue 36 (10th August 2017) - McClements, Jake; Buffone, Cosimo; Shaver, Michael P.; Sefiane, Khellil; Koutsos, Vasileios
Abstract : The self-assembly of poly(styrene- co -butadiene) random copolymers on mica surfaces was studied by varying solution concentrations and polymer molecular weights. Abstract : The self-assembly of poly(styrene- co -butadiene) random copolymers on mica surfaces was studied by varying solution concentrations and polymer molecular weights. Toluene solutions of the poly(styrene- co -butadiene) samples were spin coated onto a mica surface and the resulting polymer morphology was investigated by atomic force microscopy. At higher concentrations, thin films formed with varying thicknesses; some dewetting was observed which depended on the molecular weight. Total dewetting did not occur despite the polymer's low glass transition temperature. Instead, partial dewetting was observed suggesting that the polymer was in a metastable equilibrium state. At lower concentrations, spherical cap shaped nanodroplets formed with varying sizes from single polymer chains to aggregates containing millions of chains. As the molecular weight was increased, fewer aggregates were observed on the surface, albeit with larger sizes resulting from increased solution viscosities and more chain entanglements at higher molecular weights. The contact angles of the nanodroplets were shown to be size dependent. A minimum contact angle occurs for droplets with radii of 100–250 nm at each molecular weight. Droplets smaller than 100 nm showed a sharp increase in contact angle; attributed to an increase in the elastic modulus of the droplets, in addition, to a positive line tension value. Droplets larger than 250 nm also showed an increased contact angle due to surface heterogeneities which cannot be avoided for larger droplets. This increase in contact angle plateaus as the droplet size reaches the macroscopic scale.